Safety and efficacy of botulinum toxin type A in preventing and treating scars in animal models: A systematic review and meta‐analysis. Issue 4 (17th August 2021) - Pan, Lingfeng; Qin, Haiyan; Li, Caihong; Yang, Liehao; Li, Mingxi; Kong, Jiao; Zhang, Guang; Zhang, Lianbo
Abstract: Previous studies have used botulinum toxin type A (BTXA) to improve postoperative and hypertrophic scars; however, there is lack of detailed verification on the safety and effectiveness of this approach. This study aimed to evaluate the therapeutic effect of BTXA on postoperative hypertrophic scars and its influence on cytokine expression in animal models. A computerised search of different databases was performed, including PubMed, Web of Science, Scopus, Cochrane, Embase, CNKI, and Wanfang, up to 10 March 2021. A meta‐analysis was performed using R 4.0.0 based on hypertrophic index, epithelialisation time, wound area, and vascular endothelial growth factor (VEGF) expression. Eleven studies were included. The meta‐analysis showed a significant difference in hypertrophic index (standardised mean difference [SMD] = −2.63, 95% confidence interval [CI]: −3.50 to −1.76, P < .01), wound area (SMD = −0.54, 95% CI: −1.24 to 0.16, P < .01), and VEGF expression (SMD = −2.56, 95% CI: −3.50 to −1.62, P < .01). This study shows that BTXA is safe and effective in preventing and treating scar hypertrophy in animal models, but excessive doses of BTXA and BTXA to treat large areas should be avoided.